Choice of maintenance intravenous fluids among paediatric residents in Canada. Issue 8 (19th September 2019) - Kinlin, Laura M; Helmers, Andrew J; Friedman, Jeremy N; Beck, Carolyn E
Abstract: Background: Recent literature and guidelines support routine use of isotonic intravenous (IV) fluids for maintenance therapy in hospitalized infants and children. Current prescribing practices are unknown. Objective: To elicit paediatric residents' choice of maintenance IV fluids, particularly with regard to tonicity, in a variety of clinical scenarios and patient ages. We hypothesized that residents would choose isotonic fluids in most cases, but there would be substantially more variability in fluid choice in the neonatal age group. Methods: An Internet-based survey was e-mailed to trainees in the 17 paediatric residency programs across Canada, via the Canadian Paediatric Program Directors. The survey instrument included questions related to training, followed by a series of questions eliciting choice of IV fluid in a variety of clinical situations. Results: A total of 147 survey responses were submitted (22% response rate). Isotonic solutions were selected by >75% across all clinical scenarios involving infants and children. Very hypotonic fluids were seldom chosen. There was more variability in fluid choice in neonates, with evidence of significant differences in fluid tonicity based on senior versus junior resident status and geographical location. Conclusions: Results imply a predominance of isotonic fluid use in infants and children, suggesting that clinical practice has changed in response to risk of hyponatremia with hypotonic IV fluids. As hypothesized, there was more variability with respect to choice of maintenance fluids in neonates. This likely reflects a paucity of guidance in an age group with unique physiologic factors affecting fluid and electrolyte status.